VERB RAISING, THE IMPOVERISHMENT OF THE VERBAL PARADIGM AND THE WEAKENING OF TENSE IN BP - Tescari Neto, Aquiles (Revista do GEL, 2016)
The paper revisits the debate on verb raising in Brazilian Portuguese (BP) as well as the general discussions on the impoverishment of BP inflectional verbal paradigm. It suggests that the weakening of the inflectional system in BP is not sufficient, from both a theoretical and an empirical view, to explain why the verb raises less in BP than in other Romance languages. Rather, it suggests that the weakness of Tense in BP (AMBAR, 2008; CYRINO, 2011) should explain why V raises at most to a medial position in the Middlefield in this language. To arrive at this conclusion, the first attempt is to revisit the literature on verb movement in Brazilian Portuguese. It will be shown that there is V-to-INFL raising in this language based on traditional tests involving adverbs and floating quantifiers. The second step is to bring pieces of evidence to prove that it is not the impoverishment of the verbal paradigm in BP which explains why the verb does not raise as high as it does in the other Romance languages but rather the weakness of Tense.